A bug's life - Lasseter, John.; Stanton, Andrew; Ranft, Joe.; McEnery, Donald; Shaw, Bob.; Foley, Dave, 1963-; Spacey, Kevin; Louis-Dreyfus, Julia; Panettiere, Hayden; Diller, Phyllis; Kind, Richard; Pierce, David Hyde.; et al. ([Burbank, Calif.] : Disney/Pixar : Distributed by Buena Vista Home Entertainment, 2000)
Journey inside the miniature world of bugs where an ant named Flik hires warrior bugs to defend his colony from a horde of freeloading grasshoppers. Bonus title at end: Geri's game (Academy Award, Best Animated Short, 1997)
Rated G.
Originally produced as a motion picture in 1998.
Special features: Geri's Game (Academy Award Winning Short from Pixar); two sets of hilarious outtakes as seen in theaters.
Music, Randy Newman.
Voices of: Dave Foley, Kevin Spacey, Julia Louis-Dreyfus, Hayden Panettiere, Phyllis Diller, Richard Kind, David Hyde Pierce.
VHS; Dolby digital.
Keywords: Animated films; Animal films; Children's films; Video recordings for the hearing impaired